Curcuma longa extract reduces serum inflammatory markers and postprandial hyperglycemia in healthy but borderline participants with overweight and glycemia in the normal/prediabetes range: a randomized, double-blind, and placebo-controlled trial - Uchio, Ryusei; Okuda-Hanafusa, Chinatsu; Sakaguchi, Haruka; Saji, Ryosuke; Muroyama, Koutarou; Murosaki, Shinji; Yamamoto, Yoshihiro; Hirose, Yoshitaka (Frontiers in Nutrition, 2024)
The spice turmeric, which has the Latin name Curcuma longa (C. longa), has various physiological effects. This study evaluated the effects of a hot water mixture with supercritical carbon dioxide C. longa extracts, CLE, and the potential active components of C. longa, turmeronols A and B and bisacurone on inflammation and glucose metabolism. First, we investigated the effect of CLE and the potential active components of C. longa on lipopolysaccharide-induced inflammation in RAW264.7 macrophages. We found a significant decrease in the production of interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, and nitric oxide with CLE, turmeronol A, and bisacurone, Significant inhibition of each of these substances was also observed, except for TNF-α with turmeronol B. The second part of our work was a 12-week randomized, double-blind, placebo-controlled study in healthy but borderline adults aged 40 to 69 years with overweight and normal/prediabetes glycemia. We compared blood inflammatory and glycometabolic markers in the CLE (n = 55) and placebo groups (n = 55). We found significantly lower serum high-sensitivity C-reactive protein and hemoglobin A1c levels in the CLE group. This group also showed significant improvements in postprandial hyperglycemia and insulin sensitivity indices. Our findings indicate that CLE may reduce low-grade inflammation and thus improve insulin sensitivity and postprandial hyperglycemia. Clinical trial registration:https://center6.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000051492, UMIN-CTR, UMIN000045106.